2015
DOI: 10.1108/jes-06-2013-0085
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency and its determinants factors in Spanish textiles industry (2002-2009)

Abstract: Purpose – The purpose of this paper is to provide new evidence about the technical efficiency and its determinants in Spanish textile sector during the period 2002-2009. The empirical results suggest that the effects of trade liberalization have led to higher levels of inefficiency in the Spanish sector, due to the lack of flexibility of firms to adjust to the environment, and perhaps to aggressive competition with fuzzy rules of the game. Controlling for specific factor like age, intensity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The technical efficiency (TE) of a firm is typically decomposed into two components: pure technical efficiency (PTE) and scale efficiency (SE) (Coelli et al , 1998). Throughout the years, a stream of literature has examined firm efficiency based on the TE concept by employing parametric and non-parametric methods, but mostly in the single nation context [see, for instance Mandal and Ghosh Dastidar (2014); De Jorge-Moreno and Rojas Carrasco (2015); Demirbag et al (2016)]. Meanwhile, very few studies including Jarboui et al (2013); Jarboui et al (2014); Kinda et al (2014) and Tan et al (2019) have investigated firm efficiency in a cross-country context by documenting the findings of the different levels of firm efficiency between developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The technical efficiency (TE) of a firm is typically decomposed into two components: pure technical efficiency (PTE) and scale efficiency (SE) (Coelli et al , 1998). Throughout the years, a stream of literature has examined firm efficiency based on the TE concept by employing parametric and non-parametric methods, but mostly in the single nation context [see, for instance Mandal and Ghosh Dastidar (2014); De Jorge-Moreno and Rojas Carrasco (2015); Demirbag et al (2016)]. Meanwhile, very few studies including Jarboui et al (2013); Jarboui et al (2014); Kinda et al (2014) and Tan et al (2019) have investigated firm efficiency in a cross-country context by documenting the findings of the different levels of firm efficiency between developed and developing countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Notwithstanding, a substantial body of literature has analysed and studied the technical efficiencies of diverse range of industries all over the world using either DEA or SFA. For instance Pitt and Lee (1981); Goldar (1985); Neogi and Ghosh (1994); Ramaswamy (1994); Chandra et al (1998); Sahoo et al (1999); Jaforullah (1999); Lall and Rodrigo (2001); Sahoo and Mohapatra (2001); Rao et al (2003); Krishna (2004); Sahoo (2004); Nikaido (2004); Mukherjee and Ray (2005); Tone and Sahoo (2005); Sengupta and Sahoo (2006); Bhandari and Maiti (2007); Sahoo and Acharya (2007); Sahoo (2007, 2008); Das et al (2009); Mulwa et al (2009); Sahoo and Tone (2009a, 2009b); Bhandari and Ray (2012); Sahoo et al (2012); Mehdiloozad et al (2014); Sahoo et al (2014); Jorge-Moreno and Carrasco (2015); Goyal et al (2017) are some of the studies that have examined the technical efficiencies using DEA or SFA in various industries.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…They also highlighted that newer firms were much more efficient as compared to their older counterparts. Recently Jorge-Moreno and Carrasco (2015) undertook a study on the technical efficiency in the Spanish textile industry during 2002-2009. Here also the researchers used Cobb-Douglas functional form of SFA and highlighted that the firms in the industry were becoming inefficient due to inflexibility on the part of the firms to cope up with the dynamic global environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…2. In a different context, a study of the Spanish textile sector suggested that the effects of trade liberalization have led to higher levels of inefficiency in the Spanish sector, due to the lack of flexibility of firms and perhaps to aggressive competition (Jorge-Moreno and Carrasco, 2015).…”
Section: Unorganized Textile Industry In Maharashtramentioning
confidence: 99%